Adele Parot Beacon of the Dioclesian Lewis School of Gymnastic Expression in the American West - Barney, Robert Knight ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
In the late 1800's, Dioclesian Lewis developed and introduced into the schools his new concept of physical education. Dr. Lewis thought in terms of preventing illness and maintaining bodily strength and health through physical fitness. His "new gymnastics" were based on programs of exercise movements. Employing light equipment suitable for use by women and children, he created a system of calisthenics centered on the development of flexibility and grace of movement, rather than strength. These gymnastics could be performed in the school room and did not require large areas of space. He founded the Normal Institute for Physical Education in Boston where teachers of physical education were trained. His students spread out through the United States and foreign countries introducing the philosophy of a sound mind in a sound body to students and other teachers. One student of his, Adele Parot, carried his teaching to California. She was instrumental in bringing about California's legislation for mandatory physical education in the state's public schools, the first legislation of its type in the United States. (JD)
ERIC Note: Paper presented at the Annual Symposium of the North American Society of Sport History (1st, Ohio State University, Columbus, Ohio, May 26, 1973).
Microfiche.
Keywords: American History; Calisthenics; Educational History; Exercise (Physiology); Health Activities; Human Body; North American History; Physical Education; Physical Fitness; State Legislation; Teacher Education; Womens Athletics; Lewis (Dioclesian) -- Parot (Adele) -- United States (Far West); Speeches/Meeting Papers